Women portrayals in Warta Perdana local crime news / Wan Azfarozza Wan Athmar and Siti Faidul Maisarah Abdullah - Wan Athmar, Wan Azfarozza; Abdullah, Siti Faidul Maisarah (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2011)
The portrayal of women in television crime news can be seen as mostly negative. Women are considered newsworthy in television if they were criminals, victims, entertainers or relatives of famous men. Crime news will only generate interest when it involves women in domestic violence, rape, dowry deaths, sexual harassment or sexual abuse because it is considered as sensational stories. The aims of this research is to identify how our local news; Warta Perdana portrays women in its local crime news, the most dominant portrayal of women highlighted in its crime stories and to ascertain whether there is an agenda to portray women stereotypically in its crime news. This study utilized the qualitative research approaches which are the qualitative content analysis and in-depth interview. This research found that the most dominant portrayals of women in crime news is women as crime accomplices. Other portrayals of women highlighted in the crime news were women as victims and authoritative figure. These portrayals were not determined by any agenda instead there were based on facts, rarity and oddity of the stories.